Evaluating online health information in terms of readability, understandability and actionability - Marco Masoni; Maria Renza Guelfi (Firenze University Press, 2020)
Improving the population health literacy is one of the main objectives of 21st century medicine. Poor health literacy is associated with an inappropriate use of healthcare resources, a higher rate of unnecessary services and hospitalizations. The Internet could play an important role in increasing the level of the population health literacy. To this end, in addition to being of high quality, it is important that information provided to citizens has to be readable. Furthermore, it should be understandable and actionable, indicating clearly which actions should be taken to maintain good health. These features can be measured in online health information using validated tools such as readability formulas and the Patient Education Materials Assessment Tool, which are dealt with in this personal review. Studies that have applied these tools on online health information in english and italian language are discussed.   Valutare l'informazione sanitaria online in termini di readability, understandability e actionability Il miglioramento della health literacy della popolazione è uno degli obiettivi prioritari della Medicina del XXI secolo. Una scarsa health literacy è responsabile di una inappropriata utilizzazione dei servizi sanitari per un tasso più alto di prestazioni e di ospedalizzazioni non necessarie. Internet potrebbe svolgere un ruolo importante per aumentare il livello di health literacy nella popolazione. A tal fine è fondamentale che le informazioni sanitarie fornite ai cittadini, oltre ad essere di elevata qualità, siano comprensibili. Inoltre dovrebbero essere interpretabili (understandable) e indicare chiaramente quali azioni occorre intraprendere (actionable) per mantenere un buono stato di salute. Queste caratteristiche possono essere misurate nei materiali informativi sanitari in rete mediante strumenti validati come le formule per la readability e il Patient Education Materials Assessment Tool, oggetto di trattazione in questa revisione personale. Vengono inoltre discusse ricerche che hanno applicato questi strumenti sul materiale informativo sanitario online in lingua inglese e in lingua italiana.